Pendisiplinan Siswa Melalui Pembacaan Juz ‘Amma di Sekolah Dasar Negeri 3 Codo: Student Discipline Efforts through Reading Juz 'Amma at SDN Codo 3 - Dintia Nurmazia Milah; Handoko (STAI Ma'had Aly Al-Hikam Malang, 2023)
Student discipline cannot happen spontaneously. In an effort to improve student discipline, it is necessary to carry out a habit that is carried out repeatedly. Student discipline at Codo Elementary School 3 is carried out through reading Juz 'Amma in the morning before learning begins. This research uses a qualitative approach with the type of case study. The data collection techniques used by researchers are observation, interview and documentation techniques. The data analysis was carried out through the data reduction stage, data presentation and conclusion drawing or verification. While the data validity technique uses observation persistence and triangulation techniques and source triangulation. The results showed that: (1) The Juz 'Amma reading activity includes initial activities, core activities, and closing activities. (2) Supporting factors for the implementation of this activity include the packaging of fun activities, the active role of teachers, and the existence of adequate facilities. Meanwhile, the inhibiting factor is the lack of student awareness and the surrounding community environment. (3) The results of implementing this activity include time discipline, responsibility discipline, and discipline in enforcing rules. Kedisiplinan siswa tidak bisa terjadi secara spontan. Dalam upaya meningkatkan kedisiplinan siswa perlu dilakukan kegiatan yang berulang-ulang. Kedisiplinan siswa di SDN 3 Codo dilakukan melalui kegiatan pembacaan Juz ‘Amma di pagi hari sebelum dimulainya pembelajaran. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Teknik pengumpulan data yang digunakan peneliti adalah observasi, wawancara dan dokumentasi. Analisis data yang dilakukan meliputi tahap kondensasi data, penyajian data dan verifikasi. Sedangkan teknik validasi data menggunakan ketekunan pengamatan serta triangulasi yang meliputi triangulasi teknik dan sumber. Hasil penelitian menunjukkan bahwa (1) Kegiatan pembacaan Juz ‘Amma ini meliputi kegiatan awal, kegiatan inti, dan penutup (2) Faktor pendukung pelaksanaan kegiatan ini di antaranya adalah pengemasan kegiatan yang menyenangkan, peran aktif guru, dan adanya fasilitas yang memadai. Sedangkan faktor penghambatnya adalah lemahnya kesadaran siswa dan lingkungan masyarakat sekitar. (3) Hasil pelaksanaan kegiatan ini adalah terciptanya kedisiplinan siswa yang meliputi displin waktu, disiplin tanggung jawab, dan disiplin menegakkan aturan. Kata Kunci: Pendisiplinan Siswa, Pembacaan Juz ‘Amma, SDN 3 Codo.